2010
DOI: 10.1002/ejlt.200900180
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stability of fish oil‐enriched mayonnaise‐based salads

Abstract: The oxidative stability of fish oil-enriched mayonnaise-based salads and the influence of different vegetables in shrimp and tuna salads were evaluated. Moreover, the lipid oxidation in the presence of 1% oregano, rosemary, or thyme in fish oil-enriched tuna salad was assessed. The results obtained showed that the mayonnaise itself was more oxidatively stable without vegetables and tuna or shrimp, in spite of the higher oil content in mayonnaise (63 and 6.3% fish oil, respectively) compared to salads ($24 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…A recent study compared the oxidative stability of mayonnaise with that of mayonnaise‐based tuna and shrimp salads. The results showed that mayonnaise was more oxidative stable than mayonnaise‐based salads with different vegetables, tuna or shrimp even though the amount of oil was higher in the pure mayonnaise 12. Interestingly, this study also indicated that fish oil‐enriched mayonnaise 12 had a higher oxidative stability compared to fish oil‐enriched mayonnaises used in earlier experiments without antioxidants added 9, 10.…”
Section: Introductionmentioning
confidence: 47%
“…A recent study compared the oxidative stability of mayonnaise with that of mayonnaise‐based tuna and shrimp salads. The results showed that mayonnaise was more oxidative stable than mayonnaise‐based salads with different vegetables, tuna or shrimp even though the amount of oil was higher in the pure mayonnaise 12. Interestingly, this study also indicated that fish oil‐enriched mayonnaise 12 had a higher oxidative stability compared to fish oil‐enriched mayonnaises used in earlier experiments without antioxidants added 9, 10.…”
Section: Introductionmentioning
confidence: 47%
“…, 2005), pro‐ and antioxidative components in the ingredients present (Jacobsen et al. , 2001; Sørensen et al. , 2010a), the way the oil is delivered into the food product (Let et al.…”
Section: Introductionmentioning
confidence: 99%
“…However, these highly unsaturated lipids are prone to lipid oxidation, and their incorporation into foods is therefore limited by the development of unpleasant off-flavours. When incorporating marine oils into foods, the quality of the oil (Let et al, 2005), pro-and antioxidative components in the ingredients present (Jacobsen et al, 2001;Sørensen et al, 2010a), the way the oil is delivered into the food product (Let et al, 2007) and the processing and storage conditions of the food (Sørensen et al, 2010b) have been shown to influence the lipid oxidation in the final fish oil-enriched food product.…”
Section: Introductionmentioning
confidence: 99%
“…In fish paté, addition of omega-3 PUFA in the form of microencapsulated fish oil resulted in the most stable product, followed by pre-emulsified fish oil. In contrast, PV in fish paté with neat fish oil increased dramatically during storage at 2°C up to 12 weeks (Nielsen and Jacobsen, 2010). All fish patés contained 5% fish oil.…”
Section: Effect Of Using a Delivery Systemmentioning
confidence: 88%